2013
DOI: 10.1029/2012jd017919
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TRMM precipitation radar and microwave imager rainfall retrievals in tropical cyclone inner cores and rainbands

Abstract: [1] Tropical Rainfall Measuring Mission (TRMM) rainfall retrieval algorithms are evaluated in tropical cyclone (TC) inner cores (IC), inner bands (IB), and outer rainbands (OB). In total, 1329 IC, 2149 IB, and 4627 OB storm regions are analyzed using data from a 12-year TRMM Tropical Cyclone Precipitation Feature (TCPF) database containing 1013 TCs viewed from December 1997 to December 2009. Attention is focused on the difference between the Precipitation Radar (PR) 2A25 and the TRMM Microwave Imager (TMI) 2A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In this aspect, the TMI and PR V7 algorithms have made substantial progress in decreasing the uncertainty in retrieving global rainfall, compared to the V6 algorithms. A similar result pointing to the TMI rain relative underestimation can be found in Zagrodnik and Jiang (2013). The mean stratiform rain rates are 2.78 and 2.45 mm h 21 , respectively, for TMI and PR, showing a good agreement (12.62% difference).…”
Section: A Frequency Distributions Of Rain Intensitysupporting
confidence: 84%
“…In this aspect, the TMI and PR V7 algorithms have made substantial progress in decreasing the uncertainty in retrieving global rainfall, compared to the V6 algorithms. A similar result pointing to the TMI rain relative underestimation can be found in Zagrodnik and Jiang (2013). The mean stratiform rain rates are 2.78 and 2.45 mm h 21 , respectively, for TMI and PR, showing a good agreement (12.62% difference).…”
Section: A Frequency Distributions Of Rain Intensitysupporting
confidence: 84%
“…Cecil and Wingo (2009) showed that for rainfall, differences between microwave-only and radar retrievals could be as large as a factor of 10 for extreme instantaneous rain rates in cyclones. Recent analysis by Zagrodnik and Jiang (2013) showed that the GPROF TMI retrieval underestimates moderate to heavy rainfall (.15 mm h 21 ) when compared to rainfall algorithms derived from PR data, particularly in hurricanes. These studies indicate that for PR-based retrievals, the dynamic range is 75%-100% of the true range, whereas for the TMI-only algorithms (RSSv4 and 2A25), the dynamic range is 10%-30% of the true range.…”
Section: Observationsmentioning
confidence: 97%
“…The latter combines data from both TRMM Microwave Imager (TMI) and TRMM Precipitation Radar (PR) (Huffman et al, 2010). PR is especially useful for identifying the regions where the TMI is significantly underestimating rain rates, for example in the eyewall of the hurricanes (Zagrodnik and Jiang, 2013).…”
Section: Satellite-derived Datamentioning
confidence: 99%